3,3’-di-O-methylellagic acid, an Antioxidant Phenolics Compound from Sonneratia alba Bark - Herawati, Netti; Firdaus, Firdaus (Jurnal Natur Indonesia, 2013)
Free radicals play an important role in some pathogenesis of serious diseases, such as neurodegenerative disorders, cancer,liver cirrhosis, cardiovascular diseases, atherosclerosis, cataracts, diabetes and inflammation. Compounds that can scavengefree radicals have great potential in ameliorating these diseases. It is reported that phenolic compounds in plants possessstrong antioxidant activity and may help to protect cells against the oxidative damage caused by free radicals. Previousstudy revealed that mangrove trees, Sonneratia alba Bark showed strong antioxidant activity. Ethyl acetate fractionexhibited the best antioxidant performance. The antioxidant activity of this fraction was attributed to the presence ofcompounds of different polarities such as phenolics. Furthermore, the phenolic antioxidant of ethyl acetate fraction werepurified and identified with UV, IR, MS, and 2D NMR spectrometry. 3,3’-di-O-methylellagic acid was found in brownamourphous powder. Antioxidant activity was evaluated and compared with L-(+)-ascorbic acid as standard by usingDPPH assay. The compound has strong antioxidant activity than ascorbic acid standar with the value of IC 50 11.35 and17.64 μg/mL, respectively. The high value of antioxidant activity of compound indicate that S. alba is a potential source ofnatural antioxidant agent.